The retteng as grief therapy: Pastoral approach in the context of Toraja culture - Ismail Banne Ringgi' (Institut Agama Kristen Negeri Toraja, 2026)
Death frequently triggers a sense of alienation that underscores human vulnerability. Within the context of Torajanese society, a latent tension often arises between cultural expressions of mourning and the dogmatic formalities of Christian pastoral theology, leaving a vacuum in the management of the mourners’ psychological trauma. Addressing this issue, this hermeneutic-contextual library research marries cultural anthropology with the theology of lament to dissect retteng, a traditional Torajanese lamentation poetry, as a medium of catharsis. The objective is to uncover the therapeutic and spiritual dimensions of retteng in order to formulate a hybrid pastoral care model capable of integrating local wisdom into pastoral ministry. The analysis demonstrates that retteng operates beyond mere aesthetic boundaries; it serves as a communal space to nurture the psychological resilience of grieving families. As an intersection between cultural spirituality and faith, this poetry weaves the misery of human transience with the transcendent sovereignty of God, transforming fatalistic lamentation into a transformative proclamation of eschatological hope. Through this study, retteng is proven to possess legitimate theological healing power, making it a contextual and adaptive pastoral instrument. Integrating this tradition into pastoral ministry will revitalize a grounded faith, where local cultural expressions are elevated into profound acts of faith that restore the community in Christ.